Literacy Coursework in Speech-Language Pathology Graduate Programs: An Exploration of 50 Programs. - Yi, Julia J.; Erickson, Karen A. (Perspectives of the ASHA Special Interest Groups, 2024)
Purpose: The purpose of this study was to examine the occurrence of preservice literacy coursework in a sample of graduate speech-language pathology programs in the United States and to investigate the relationship between the likelihood that programs offered literacy coursework and (a) geographical region, (b) Carnegie Classification of research activity, and (c) U.S. News & World Report ranking. Method: Course offerings were analyzed from a sample of 50 accredited speech-language pathology graduate programs that were selected through stratified random sampling using the strata of U.S. geographical regions and the Carnegie Classification of research activity. Results: Only 28% (n = 14) of the programs in the sample offered a course dedicated to literacy, 42% (n = 22) offered a course that embedded literacy content, and 14% (n = 7) offered both a course dedicated to literacy and a course that embedded literacy content. Descriptions of courses dedicated to literacy were at least 60% more likely to specifically reference training in literacy assessment or intervention than the descriptions of courses that embedded literacy content. Region, Carnegie Classification, and U.S. News & World Report ranking did not significantly predict the likelihood of programs offering literacy courses. Conclusion: This study corroborates surveys of speech-language pathologists regarding their preservice literacy training and reveals the continued need to increase preservice coursework focused on literacy in speech-language pathology graduate programs, ideally through courses that are dedicated to literacy and address both literacy assessment and treatment.